Testing and modelling of soft connective tissues of joints: a review - Masouros,SD; Parker,KH; Hill,AM; Amis,AA; Bull,AMJ (Journal of Strain Analysis for Engineering Design, 2009)
There is wealth of data from experimental and numerical methods of analysing and modelling soft connective tissues of joints. In recent years, the advances in computational and technological capabilities allowed for several aspects of the function and mechanical behaviour of soft connective tissues of joints to be explored. However, the nature of soft tissue poses a great challenge in characterising its material behaviour in a repeatable and physiologically or clinically relevant manner. This review article attempts to present, critique and suggest experimental and numerical methods that are associated with the function and mechanical response of soft connective tissues of joints.